Global research productivity in the field of discectomy on lumbar disc herniation: A systematic bibliometric analysis - Li, Wei-Shang; Yan, Qi; Li, Gao-Yu; Chen, Wen-Ting; Cong, Lin (Frontiers in Surgery, 2023)
Abstract Objective: To evaluate the global research productivity in the field of discectomy on lumbar disc herniation (LDH) through bibliometric analysis and mapping knowledge domains. Methods: A systematic literature search was performed on the Web of Science (WoS), including the Science Citation Index Expanded (SCIE) database and PubMed. The number of publications, countries of publications, journals of publications, total citation frequency, impact factors of journals and Institution sources were analyzed by Microsoft Excel 2019, Online Analysis Platform of Bibliometrics and VOSviewer. Hotspots were also analyzed and visualized based on VOSviewer. Results: A total of 2066 papers were identified. The United States ranked first in the number of total citations (7970). China ranked first in the number of publications (556, 26.9%), which has surpassed the United States in terms of the number of publications published annually since 2016. Wooridul Spine Hospital published the most papers (43). And for journals, Spine has published the largest number of papers (289) in this field with the most citation frequencies (6607). Hotspots could be divided into three clusters: surgery, lumbar disc herniation, diagnoses. The most recent topic appeared was symptomatic re-herniation. Conclusions: The United States is the most significant contributor to the development of discectomy on LDH. The current research focus of discectomy on LDH were the comparison between surgical approaches and evaluation of current minimally invasive discectomy. At present, minimally invasive technique such as endoscopic discectomy, cannot completely replace non-endoscopic discectomy (open discectomy and microdiscectomy) through bibliometric analysis and mapping knowledge domains.